The Psychometric Properties of the Norwegian version of Development and Well-being Assessment (DAWBA) - Brøndbo, Per Håkan; Martinussen, Monica (PsykTestBarn, 2013)
Description: Development and Well-Being Assessment (DAWBA) was developed in the 90’s in Great Britain as a diagnostic tool to assess common diagnoses among children and young people (DSM-IV) (Goodman et al., 2000). It was translated to Norwegian by Einar Heiervang, Kjerstin Søvik, Melanie Young, Anne Karin Ullebø and Ingrid Jangård Orre. DAWBA exists in three different versions; for parents, adolescents, and teachers which may be administered online or in person. The Norwegian version includes questions related to a large number of problems and disturbances in addition to background information and the child’s resources. It takes approximately 50 minutes for the parents to answer the questions. Relevant education and training is required in order to use the DAWBA. The diagnostic system may be used for both clinical and research purposes. Literature search: The systematic search resulted in 33 articles where a total of eight fulfilled the inclusion criteria. The included articles reported results from two studies. The first was “Children in Bergen” with a sample from the general population (Heiervang, et al., 2007), and the second was a clinical study based on children and young people referred to outpatient treatment (Brøndbo et al., 2012). Psychometrics: The included studies reported the prevalence of diagnoses both in a clinical sample and among children living in Bergen. One study examined the inter-rater reliability between different clinicians using the DAWBA, with a large degree of consistency for most diagnoses. Some articles provided results relevant to the validity of DAWBA, e.g., by examining DAWBA diagnoses with diagnoses determined by clinicians without using the DAWBA, or by comparing data-generated DAWBA diagnoses with diagnoses determined by clinicians using the DAWBA. Conclusion: The Norwegian version of DAWBA may be a useful tool in ordinary clinical practice when diagnosing mental health problems among children and young people. The documentation indicated that the computer generated diagnoses should only be used for research purposes to provide prevalence estimates.